Coordination Strategy of Dual-Channel Supply Chain for Fresh Product Under the Fresh-Keeping Efforts - Zhang, Kejing; Gao, Jingkai (International Journal of Emerging Trends in Social Sciences, 2018)
In the context of high loss in the storage and transportation of fresh agricultural products, in order to help company make reasonable fresh-keeping decisions and reduce losses, we established a leading supplier of fresh agricultural products in two level dual channel supply chain model based on consumer utility function, and using Stackelberg game method to solve the optimal pricing and optimal fresh-keeping decision of fresh agricultural supplier and retailer under centralized decision-making and decentralized decision-making model. Research shows: (1) Under centralized decision-making model, the highest profit does not affect the cooperation and achieve complete coordination regardless of the bargaining power of the retailer; (2) High cost factor of fresh-keeping efforts makes supplier and retailer more inclined to lower prices to attract consumers. (3)The “revenue sharing + fresh-keeping cost sharing” coordination strategy provided by the supplier can increase the respective profits of both parties and achieve complete coordination of the dual-channel supply chain of fresh agricultural products.